1992
DOI: 10.1007/bf00180741
|View full text |Cite
|
Sign up to set email alerts
|

Disturbed calcium metabolism in subjects with elevated diastolic blood pressure

Abstract: Essential hypertension has been associated with disturbed calcium metabolism, but the available data are controversial. We measured parameters of calcium metabolism in groups of untreated male subjects (n = 78) with elevated diastolic blood pressure (101 +/- 6 mmHg, mean +/- SD) and age-matched male subjects (n = 79) with low diastolic blood pressure (62 +/- 4 mmHg). The participants of the study were drawn from a random population sample. Subjects with high diastolic blood pressure had significantly higher ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…While the serum ionized calcium levels are comparable in both groups as there is no significant difference. This is in agreements with studies of K. Sudhakar et al 1 and Reichel et al 6 Serum calcium levels were also found to be significantly lower by Fu. Y., Wang et al 14 and Touyz.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…While the serum ionized calcium levels are comparable in both groups as there is no significant difference. This is in agreements with studies of K. Sudhakar et al 1 and Reichel et al 6 Serum calcium levels were also found to be significantly lower by Fu. Y., Wang et al 14 and Touyz.…”
Section: Discussionsupporting
confidence: 93%
“…Individuals with high diastolic blood pressure had significantly lower total serum calcium. 6 The free intracellular calcium concentration determines the tension in vascular smooth muscle cells thereby resulting in peripheral vascular resistance. 1 Zidek et al found an increased intravascular calcium concentration in normotensive subjects with familial hypertensive disposition in comparison with Normotensives without family history of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…In the third National Health and Nutrition Examination Survey (NHANES III), a large (n = 12,644) study representative of the US civilian population, there was a significant inverse correlation between systolic BP and pulse pressure with 25(OH)D3 levels [90]. Although similar findings were replicated by many investigators [105][106][107][108][109][110][111][112][113], this association was not confirmed by others, [81,[92][93][94][95][96][97][98] most of which, however, included fewer participants than NHANES III [92][93][94][95][96][97]. Overall, despite the inconsistent findings among cross sectional studies, the majority of those with large sample sizes demonstrated an inverse relationship between 25(OH)D3 levels and BP [116].…”
Section: Vitamin D and The Individual Components Of Mets Hypertensionmentioning
confidence: 80%
“…The results of the trials which investigated the association between BP and circulating 1,25(OH) 2 D3 levels are also inconsistent [43,53,97,[99][100][101][122][123][124][125]. 1,25(OH) 2 D3 concentration mainly depends on calcium homeostasis, may be confounded by renal function and does not accurately represent whole body vitamin D status [19,20].…”
Section: Vitamin D and The Individual Components Of Mets Hypertensionmentioning
confidence: 99%
“…Briefly, we identified 58 potentially relevant articles on blood 25(OH)D concentrations in relation to BP. Eighteen studies were excluded because no RR or OR of hypertension was reported [3,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. We further excluded 22 studies with data on blood pressure only (not hypertension) , one study including only adolescents [54], and two articles because of duplicate reports from the same study population [55,56].…”
Section: Literature Searchmentioning
confidence: 97%